Characteristic analysis of acoustic emission monitoring signal in coal seam hydraulic fracturing - LI Baolin; WANG Enyuan; LI Nan; GAO Qinqiong; ZHOU Ming (Gong-kuang zidonghua, 2015)
In order to promote application of acoustic emission monitoring technology in effect evaluation of coal seam hydraulic fracturing, coal seam hydraulic fracturing process was monitored by use of coal and rock dynamic disaster acoustoelectric monitor, and characteristics of acoustic emission signals collected in the process were analyzed through fourier transformation and wavelet packet analysis. The field test results show that main frequency of effective acoustic emission signals of coal seam hydraulic fracturing is in 470-1 700 Hz, which is lower than main frequency of underground noise interference signal. Energy distribution of the effective acoustic emission signals of coal seam hydraulic fracturing is concentrated in 0-5 000 Hz with proportion 86.5%-95.4%, and the energy distribution of effective signals is concentrated in low frequency band such as 312.5-625, 625-937.5, 937.5-1 250, 1 875-2 187.5 Hz.